Association between inflammatory markers in induced sputum and clinical characteristics in children with non-cystic fibrosis bronchiectasis - KARADAĞ, BÜLENT TANER; GÜRAN, TÜLAY (WILEY-LISS, 2007)
To study clinical, radiological and laboratory features of children with non-cystic fibrosis (non-CF) bronchiectasis (BE) and the association between symptom scores, spirometry, high-resolution computed tomography (HRCT) findings and inflammatory markers in induced sputum in these children. Twenty-seven children with steady-state non-CF BE were cross-sectionally evaluated by symptom scores, pulmonary function tests, anatomic extension and severity scores of BE in HRCT and tumor necrosis factor-alpha (TNF-alpha) and interleukin-8 (IL-8) levels in induced sputum. There were 16 girls and 11 boys. Median (interquartile range) age of study group was 11.4 (9.5-13.6) years, follow-up duration was 3.5 (2-6.5) years and symptom scores were 4 (3-6). Pulmonary function tests revealed FEV1 of 82%pred (72-93), FVC of 82%pred (74-92), and FEF25-75% of 82%pred (68-95). According to anatomic extent of BE on HRCT; 2 patients had mild, 4 had moderate and 21 had severe BE. Based on severity scores of HRCT; 10 patients had mild, 10 had moderate and 7 had severe BE. Neutrophils consisted 29.9% (14.9-53.7) of the total leucocytes in induced sputum samples. Sputum concentration of TNF-alpha was 58 pg/ml (9.2-302) while IL-8 concentration was 2.7 ng/ml (1.7-2.8). Symptom scores correlated with FEV1 and sputum IL-8 levels (r=-0.49, r=0.67, P < 0.05). There was a significant correlation between HRCT severity scores and symptoms, FEV1, sputum IL-8 and TNF-alpha levels (r=0.64, r=-0.68, r=0.41, r=0.41, respectively, P < 0.05). In children BE is associated with ongoing inflammation. This inflammation can be reliably monitored by radiological scores, spirometry, as well as sputum inflammatory markers. Follow-up of children with BE using these clinical tools may improve patient care.
Keywords: bronchiectasis; children; HRCT; induced sputum; TNF-alpha; IL-8; STEADY-STATE BRONCHIECTASIS; NON-CF BRONCHIECTASIS; NECROSIS-FACTOR-ALPHA; COMPUTED-TOMOGRAPHY; INHALED FLUTICASONE; AIRWAY INFLAMMATION; ORPHAN DISEASE; LUNG-FUNCTION; NEUTROPHILS; INDUCTION